Neuromyelitis Optica Spectrum Disorder with Tumefactive Demyelination mimicking Multiple Sclerosis: A Rare Case - Roy, Ujjawal; Saini, Dinesh Satyanarayan; Pan, Koushik; Pandit, Alak; Ganguly, Goutam; Panwar, Ajay (Frontiers in Neurology, 2016)
Neuromyelitis optica spectrum disorder (NMOSD) is a diverse condition which not only encompasses isolated longitudinally extensive transverse myelitis and optic neuritis but also includes area postrema syndrome, acute brainstem syndrome, symptomatic narcolepsy or acute diencephalic clinical syndrome, and symptomatic cerebral syndrome. Imaging may reveal periependymal lesions surrounding the ventricular system or involvement of corticospinal tracts, area postrema, diencephalon and corpus callosum. Rarely there may be hemispheric tumefactive lesions which enhance in a “Cloud-like” fashion on gadolinium injection unlike in tumefactive multiple sclerosis where there is incomplete ring enhancement. Here, we present a case of aquaporin-4 positive relapsing NMOSD who presented to us with recurrent episodes of paraperesis with longitudinally extensive transverse myelitis and tumefactive lesions of brain on imaging which enhanced in an incomplete ring like pattern resembling multiple sclerosis.